Adequacy of the Global Financial Safety Net-Considerations for Fund Toolkit Reform. (Policy Papers; Policy Paper ;, 2017)
liquidity in the face of increased vulnerabilities calls for enhancing the liquidity support provided through the global financial safety net (GFSN). The global economy is experiencing a period of protracted uncertainty, marked by frequent episodes of volatility. Demand for liquidity has intensified, in particular from emerging markets, which are experiencing a build-up of vulnerabilities and the depletion of their fiscal buffers. The enhanced GFSN meets only partially this higher demand for liquidity. The IMFC and G20 have called on the Fund to further strengthen the safety net. The uneven use of the Fund's toolkit for crisis prevention suggests the need to reconsider its design. Despite a major overhaul of the Fund's lending instruments available for precautionary financing, only a modest number of countries have used them. In particular, the lack of access to a liquidity backstop for members with strong policies-similar to the standing bilateral swap arrangements (BSAs) among central banks-limits the availability of Fund support over the whole duration of the shock during protracted periods of global uncertainty. Moreover, the need to resort to Fund financing still carries a high political cost (stigma) for some members. To enhance further the Fund's toolkit for crisis prevention, consideration could be given to revisiting the existing toolkit and introducing new instruments. The toolkit could thus be enhanced by: establishing a new facility for precautionary financing that would provide a "standing" liquidity backstop to members with strong fundamentals and policies for use when hit by liquidity shocks; and adjusting the existing toolkit to maintain cohesion. Any change to the Fund toolkit would need to take into account the tradeoffs between reducing stigma and containing moral hazard, while simultaneously safeguarding Fund resources. A Fund policy monitoring instrument could improve the cohesion of the global safety net. As the GFSN has expanded and become more multi-layered, there is a need to improve cooperation across the different layers to unlock financing and signal commitment to reforms. Creating a policy monitoring instrument that is available to all Fund members could help in this regard. Next steps . In light of Directors' views on these points, staff could come back with subsequent papers that lay out specific and detailed proposals for reforming the lending toolkit. While these papers focus on the GRA lending toolkit, a separate forthcoming paper will assess some aspects of the concessional lending toolkit.